Begegnungsschule und Fremdsprache: Der pädagogisch-institutionelle Diskurs in Bezug auf die mehrsprachige und plurikulturelle Kompetenzförderung in einer deutschen Auslandsschule - Carapeto-Conceição, Robson (Verbum, 2018)
[full article, abstract in German; abstract in English] Im Kapitel 8 des Gemeinsamen europäischen Referenzrahmens für Sprachen (GER) wird die sogenannte mehrsprachige und plurikulturelle Kompetenz als weiteres Ziel des Sprachenlernens erläutert. Dementsprechend wird die allgemeine Sprachkompetenz „nicht als Schichtung oder als ein Nebeneinander von getrennten Kompetenzen verstanden, sondern vielmehr als eine komplexe oder sogar gemischte Kompetenz“ (Trim et al. 2001, p. 163) betrachtet. Insgesamt werden 140 Auslandsschulen mit Ressourcen des deutschen Auswärtigen Amtes in 71 Ländern gefördert. Von 80.000 Schülern besitzen ca. 73% weder die deutsche Staatsbürgerschaft noch sprechen sie Deutsch als Erstsprache. Meistens handelt es sich um private Bildungsanstalten, welche als bikulturelle Begegnungsschulen bezeichnet und von Kindern und Jugendlichen aus ökonomisch privilegierten Elternhäusern besucht werden. In diesem Zusammenhang stellt sich die Kernfrage: Inwiefern entspricht der dabei erwartete interkulturelle Dialog den Austauschdynamiken und Identitätsprozessen, wie sie im Schulalltag festgestellt werden können, und auch den Prämissen des GER in Bezug auf interkulturelle und mehrsprachige Kompetenz? An welcher sprachlichen Ideologie orientiert sich der Diskurs und die pädagogische Praxis in solchen binationalen Schuleinrichtungen? Die Analyse des institutionellen Diskurses der untersuchten Einrichtung zeigt ihren ideologischen Unterbau und die soziopolitische Zielgruppe auf, die sie in den Blick nimmt, sowie ihre Einstellung zu Interkulturalität und Mehrsprachigkeit. Die überwiegende Spracheinstellung verweist noch auf den „Nativitätsmythos“ (Rajagopalan 1997, p. 226 f.), indem die Sprachkompetenz des zweisprachigen Individuums hinsichtlich eines anachronistischen, imaginären ‚Muttersprachlers‘ bewertet wird. Encounter Schools and Foreign Language: The Pedagogical-Institutional Discourse about Multilingual and Pluricultural Competence Promotion in a German School Abroad Among the 80,000 students attending the 140 German schools abroad, about 73% are not German or ‘native’ German speakers. These are usually private schools, called “bicultural schools of encounter” frequented by children and young people from the economically privileged classes. The purpose of this study is to analyze the permeability of the space of this encounter and between the internal structures of the same. We seek to elucidate the extent to which the model of intercultural dialogue envisaged by this political project corresponds to the dynamics of exchanges and identity re-elaborations that occur organically and to the assumptions of the Common European Framework of Reference for Languages (CEFR) in relation to the development of intercultural and plurilingual competences. Analyzing the presentation of the institutional profile and pedagogical plan in the homepage of one of these schools, we hope to counter the vestiges of this proposal of literacy in the school environment to the social and linguistic representations shared by these institutions and their target audience. In this context, the key question arises: To what extent does the expected intercultural dialogue correspond to the exchange dynamics and identity processes that can be identified in everyday school life, and to the premises of the CEFR in relation to intercultural and multilingual competence? At which linguistic ideology is the discourse and pedagogical practice in such binational institutions oriented? The analysis of the institutional discourse of a bilingual German school located in Brazil aims to reveal its ideological substructure and the socio-political target group that it looks at, as well as its attitude to interculturality and multilingualism. According to the results, the predominant language attitude still refers to the "myth of nativity" (Rajagopalan 1997: 226 f.), in which the linguistic competence of the bilingual individual is evaluated in terms of an anachronistic, imaginary ’native speaker’. The theoretical basis for this study is presented in the first two chapters, followed by a brief discussion of the methodology applied on this research. Afterwards, chapter 5 deals in depth with the institutional discourse on the examined school concept. Chapter 6 deals with language attitudes and transcultural processes in reports on multidisciplinary activities and the following concluding chapter tries to reconstruct the challenges of a partly organic, partly planned development towards a multilingual (school) identity.